2019
DOI: 10.1590/fst.28217
|View full text |Cite
|
Sign up to set email alerts
|

Microbial characterization and diversity of artisanal Ranchero cheese with emphasis in Lactococcus strains

Abstract: The aim of this work is to characterize the natural microflora of artisanal Ranchero cheese and to identify Lactococcus isolates. Ten artisanal Ranchero cheese samples made with raw milk were obtained from local producers located in different geographical areas. Aerobic mesophilic, Staphylococci, Psychrophilic, total coliforms, molds, yeast and, lactic acid bacteria (LAB) (Lactococcus, Streptococcus mesophilic and thermophilic, Lactobacillus, Enterococcus, Leuconostoc) were numbered through agar plating. LAB i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…These microorganisms are normally undesirable in soft cheeses, but to some extent, they may positively contribute to the aroma of traditional cheeses. It should be noted that fungi and yeasts may not only deteriorate characteristics of cheese but also pose a risk to public health [ 4 , 30 ]. Although the results show that there was an interesting effect, there are still no reports of the antifungal effect of xoconostle to corroborate these findings.…”
Section: Discussionmentioning
confidence: 99%
“…These microorganisms are normally undesirable in soft cheeses, but to some extent, they may positively contribute to the aroma of traditional cheeses. It should be noted that fungi and yeasts may not only deteriorate characteristics of cheese but also pose a risk to public health [ 4 , 30 ]. Although the results show that there was an interesting effect, there are still no reports of the antifungal effect of xoconostle to corroborate these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Martínez et al (2020) also confirmed the occurrence of staphylococcal enterotoxin genes by PCR in samples of fresh cheese marketed in Cuba. Gallegos-Acevedo et al (2019) reported a high number of mesophilic and psychrotrophic bacteria, total coliforms, Staphylococcus bacteria and molds in artisanal Ranchero cheeses made with raw milk and obtained from local producers in Mexico. Sanitation deficiencies in the production of artisanal Ranchero cheese were evident, which may translate into being a potential consumers health risk factor.…”
Section: Resultsmentioning
confidence: 99%
“…In the past, Brevibacterium linens was considered to be the sole microorganism responsible for the color development at the surface of the cheeses because of its ability to produce orange carotenoids [ 37 ]. Other bacteria including cream-colored and yellow-pigmented coryneform were lately identified to be as significant as B. linens for the ripening of the cheese rind [ 25 , 30 , 37 , 38 , 39 , 40 ]. According to Bockelmann, 2002 [ 41 ], the color development of typical light-brown cheese such as Tilsit, Chaumes, Limburger, and Romadour was attributed to the interactions between yellow-pigmented A. nicotianae and other microorganisms while the orange-pigmented B. linens were found less significant.…”
Section: Significance Of Arthrobacter Spp In the D...mentioning
confidence: 99%